Essentials of Chinese Medicine Volume 3 - Liu, Zhanwen (Springer London : Imprint: Springer, 2009)
The modern medical model is gradually shifting from one of biomedicine to one that integrates practices from the physiological, psychological, sociological and medical fields. This growing recognition that people, the environment, ecological conditions and society are all aspects of a united whole has given rise to an emergence of alternative medicine and therapies, many of which are borrowed from traditional Chinese medicine. Volume Three elucidates the treatments of Chinese Medicine for commonly encountered diseases in internal medicine, surgery, gynecology, pediatrics, ophthalmology and otorhinolaryngology. The authors present supplementary case studies, which helpfully augment the reader's grasp of the traditional Chinese medical approach to these conditions.